2023
DOI: 10.1002/jcsm.13194
|View full text |Cite
|
Sign up to set email alerts
|

Dietary phosphate restriction prevents the appearance of sarcopenia signs in old mice

Abstract: Background Sarcopenia is defined by the progressive and generalized loss of muscle mass and function associated with aging. We have previously proposed that aging-related hyperphosphataemia is linked with the appearance of sarcopenia signs. Because there are not effective treatments to prevent sarcopenia, except for resistance exercise, we propose here to analyse whether the dietary restriction of phosphate could be a useful strategy to improve muscle function and structure in an animal model of aging. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Phosphate levels rise during aging, and it has been shown that in aged mice elevated serum phosphate levels associate with reduced muscle strength [262,263]. Furthermore, aged mice receiving a low-phosphate diet show improved muscle function, with larger myofiber area, less fiber type switching, and reduced fibrosis, as well as increased muscle strength and physical performance [263,264]. Combined, these in vivo studies suggest that rises in extracellular phosphate level can impair the myogenesis and the growth of myofibers, alter metabolic activity of skeletal muscle tissue, and promote inflammation.…”
Section: Phosphate and Sarcopeniamentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphate levels rise during aging, and it has been shown that in aged mice elevated serum phosphate levels associate with reduced muscle strength [262,263]. Furthermore, aged mice receiving a low-phosphate diet show improved muscle function, with larger myofiber area, less fiber type switching, and reduced fibrosis, as well as increased muscle strength and physical performance [263,264]. Combined, these in vivo studies suggest that rises in extracellular phosphate level can impair the myogenesis and the growth of myofibers, alter metabolic activity of skeletal muscle tissue, and promote inflammation.…”
Section: Phosphate and Sarcopeniamentioning
confidence: 99%
“…Finally, administration of a low-phosphate diet has been shown to improve skeletal muscle atrophy in Col4a3 −/− mice [110], suggesting that in this CKD model the injury might be caused by the hyperphosphatemia. Furthermore, phosphate levels rise during aging, and it has been shown that aged mice receiving a low-phosphate diet have improved muscle function, with a larger cross-sectional area of myofibers and reduced fibrosis [264]. Future human studies should determine the potential protective effects of a low-phosphate diet on skeletal muscle tissue in CKD patients or the elderly.…”
Section: Nutrition As Therapy For Ckd-associated Sarcopeniamentioning
confidence: 99%
“…For example, in 2018, researchers from the Republic of China found that serum phosphate levels within the high end of the normal range were associated with age-related loss of muscle strength, or dynapenia, in an analysis of U.S. NHANES data [91]. Additionally, a 2023 study in the Journal of Cachexia, Sarcopenia and Muscle found that feeding geriatric mice a low-phosphate diet lowered the serum phosphate of the mice to levels approaching serum levels in younger mice [92]. Remarkably, compared to geriatric mice fed a standard diet three-times higher in phosphate, the muscle mass measured in the gastrocnemius and tibialis of the geriatric mice receiving the low-phosphate diet increased by 44%, along with increases in strength and physical performance.…”
Section: Cancer Cachexia Protein and Dietary Phosphatementioning
confidence: 99%
“…The expression of atrogin‐1 in old animals fed with the low‐phosphate diet is lower. In addition, skeletal muscle fibrotic regions in aged mice fed with a low-phosphate diet showed a considerable reduction, suggesting that age-related fibrosis could be delayed by a decreased serum phosphate concentration [ 215 ].…”
Section: The Interplay Between Mitochondria Ros and Ecmmentioning
confidence: 99%